Processos educativos e emancipação: a visão dos educadores sociais sobre suas práticas - Menezes, Maria Cecilia Kerches de [UNESP] (2015)
This study aimed to analyze whether for professionals who develop educational activities in social practices, their practices are constituted as an emancipatory action. It is a qualitative research which used two data collection instruments: document analysis and semi-structured interviews with professionals / social workers who work in a social project in a city of São Paulo. The study is anchored on historical dialectic materialism and historical cultural perspective when analyzing the company and its structural contradictions with an educational system geared to the formation of submissive and uncritical individuals, considering the capital world of logic. Initially contextualizes the state's role in its broad sense in human development. Then shows the trajectory of the Brazilian social assistance to get to be recognized as a public policy, it is in this scenario that is the phenomenon studied. And following is a reflection on non-formal education, considering that the emancipatory educational practice should be part of a totality of educational activities. With the data, it was built four categories of analysis in which it is evident that the meanings constructed on emancipation are based on the formation of submissive individuals to capital. This indicates the need to create opportunities and possibilities for those professionals to review their conceptions of other optics because only through educational basis of shares will be possible to understand the essence of the working dynamics of this society and intervene in the design and implementation of more equitable policies in the field of social assistance